Strategies for resolving challenging psychedelic experiences: insights from a mixed-methods study - Maximillian J. Wood; Rosalind G. McAlpine; Sunjeev K. Kamboj (Scientific Reports)
Abstract Psychedelic substances are garnering renewed interest for their potential therapeutic applications, yet the mechanisms by which challenging experiences during psychedelic use contribute to positive outcomes remains poorly understood. Here we present a mixed-methods investigation into the strategies individuals employ to navigate difficult psychedelic experiences and their relationship to emotional breakthrough. Qualitative analysis of accounts from psilocybin retreat participants (n = 16) informed the development of the Responses to Challenging Psychedelic Experiences Inventory (ReCiPE). In a subsequent online survey (n = 529), exploratory factor analysis of the ReCiPE revealed three primary response strategies: Acceptance and Reappraisal, Sensory Regulation and Physical Interaction, and Social Support and Disclosure. Exploratory correlation and multiple regression analyses demonstrated significant relationships between different types of challenges, response strategies and emotional breakthrough. Notably, Acceptance and Reappraisal, and Social Support and Disclosure strategies were positively associated with greater emotional breakthrough. Fear-related challenges were negatively associated with emotional breakthrough and involved fewer adaptive coping strategies. These findings elucidate the complex interplay between challenging experiences and adaptive responses in psychedelic contexts, offering insights for optimising therapeutic protocols and enhancing safety in both clinical and non-clinical settings.